Acid suppression in patients treated with endoscopic therapy for the management of gastroesophageal varices: a systematic review and meta-analysis. (3rd June 2018) - Zhu, Jia; Qi, Xingshun; Yu, Haonan; Su, Chunping; Guo, Xiaozhong
ABSTRACT: Background and aim : Endoscopic therapy is the cornerstone choice for the management of varices and variceal hemorrhage. The aim of the present systematic review and meta-analysis was to evaluate the efficacy of acid suppression in patients treated with endoscopic therapy for gastroesophageal varices. Methods : All eligible studies were searched via the PubMed, EMBASE, and Cochrane Library databases. Incidence of bleeding, mortality, ulcers, chest pain, and dysphagia after endoscopic therapy and length of stay were analyzed. Subgroup analyses were performed according to the types and major indications of endoscopic treatments. Odds ratios (ORs) with 95% confidence intervals (95%CIs) were calculated. Results : Nine studies with 1470 patients were included. Acid suppression could significantly decrease the incidence of bleeding (OR = 0.39, 95%CI: 0.19–0.81, P = 0.01) and diminish the ulcer size (OR = 0.78, 95%CI: 0.38–1.57, P = 0.48) after endoscopic therapy. The subgroup analyses showed that acid suppression could significantly decrease the incidence of bleeding in patients undergoing prophylactic EVL, rather than in patients undergoing therapeutic EVL. There was no significant difference in the incidence of mortality, ulcers, chest pain, and dysphagia and length of stay between patients treated with and without acid suppression. Conclusion : Acid suppression might be considered in patients undergoing prophylactic EVL for gastroesophageal varices.